Dietary patterns and stable isotope ecology of sympatric Verreaux’s sifaka (Propithecus verreauxi) and ring-tailed (Lemur catta) inhabiting the Beza Mahafaly Special Reserve - Sawyer, Nora W (East Carolina University)
Primatologists have long been captivated by the study of the inter-relationships between nonhuman primate (NHP) biology, behavior, and ecology. To understand these interplays, primatologists have developed a broad toolkit of methodologies including behavioral observations, controlled studies of diet and physiology, nutritional analyses of NHP food resources, phylogenetic reconstructions, and genetics. Relatively recently, primatologists have begun employing stable isotope analyses to further our understanding of NHPs in free-ranging settings. Stable carbon ([delta]¹³C) and nitrogen ([delta]¹⁵N) isotope values are recorded in the tissues and excreta of animals and reflect their dietary patterns. This study incorporates the [delta]¹³C and [delta]¹⁵N fecal values of the ring-tailed lemurs (Lemur catta) and Verreaux's sifaka (Propithecus verreauxi) that inhabited the Beza Mahafaly Special Reserve in southwest Madagascar. The statistical program R was used to measure the impacts of anthropogenic disturbance and season (wet vs. dry) on the [delta]¹³C and [delta]¹⁵N fecal values of these primates. Furthermore, this project attempted to measure the accuracy of using feeding observations in comparison to stable isotope analysis to infer diet. In order to do so, this project integrated the feeding observations of L. catta and P. verreauxi with the [delta]¹³C and [delta]¹⁵N values of the plants they ate and compared these vales to their [delta]¹³C and [delta]¹⁵N fecal values. Based on feeding observations and [delta]¹³C and [delta]¹⁵N plant values, an equation was developed to predict the fecal [delta]¹³C and [delta]¹⁵N values of the ring-tailed lemurs and Verreaux's sifaka. However, the predicted fecal values did not always align accurately with those that were observed. Nonetheless, the [delta]¹³C and [delta]¹⁵N values reflected diverging dietary trends and differences in habitat use patterns among the social groups of the ring-tailed lemurs and Verreaux's sifaka at the reserve. Thus overall, the results of this study demonstrated that both primates partition their resources differently, allowing them to live in sympatric associations. Ultimately, these data are useful for modeling Malagasy lemur behavior, especially those species or populations which are severely impacted by human behavior.
Keywords: Lemurs--Nutrition--Madagascar; Lemurs--Behavior--Madagascar; Ring-tailed lemur--Nutrition--Madagascar; Verreaux's sifaka--Nutrition-- Madagascar